Relationship between increased body weight and oral health in children - Janković, Svjetlana; Ivanović, Mirjana; Carević, Momir; Davidović, Bojana; Tomić, Slavoljub; Lečić, Jelena (Vojnosanitetski pregled, 2021)
Backgraund/Aim. Increased body weight in childhood may have negative effects on many tissues and organs in the body. The aim of this study was to determine whether the state of oral health in children with increased body mass is different from the children with normal body weight. Methods. The study included 190 children, aged 6 to 15 years. Assessment of nutritional status of subjects was performed by the use of Body Mass, and the respondents were divided into a group of increased body weight children (IWC) and a group of normal body weight children (NWC). Hard dental tissue state of health was assessed by the decayed, missing and filled teeth (DMFT) index. The gingival health was assessed using gingival index (GI). Community Periodontal Index (CPI) was used for the assessment of periodontal tissue. The oral hygiene was assessed using the Simplified Debris (Plaque) Index Greene-Vermilion. Results. Average DMFT value in the IWC group was 5.01 ± 2.4, and in the NWC 4.43 ± 2.0; (p > 0.05). GI values in the IWC group was 0.64 ± 0.37, while in the NWC group it was 0.55 ± 0.35 (the difference was not statistically significant). Average CPI index values were 1.33 ± 0.49 in the IWC group and 0.77 ± 0.61 in the NWC group and statistically significant differences were observed concerning periodontal tissue state of health. The GV index values in the IWC group were 1.01 ± 0.49, and in the NWC group 0.89 ± 0.45; it was not statistically significant. Conclusion. Results of this research do not indicate that children with increased body weight have more affected teeth. However, they have a worse condition of periodontal tissue in comparison to normal weight children.
Keywords: body weight; child; body mass index; obesity; periodontal index; oral hygiene; tooth.